STRUKTUR ORGANISASI DAN PENGELOLAAN BADAN USAHA MILIK NEGARA (BUMN): PERAN MENTERI SEBAGAI WAKIL PEMEGANG SAHAM, TANGGUNG JAWAB DIREKSI, DEWAN KOMISARIS, DAN DEWAN PENGAWAS DALAM MEWUJUDKAN TATA KELOLA PERUSAHAAN YANG BAIK (GOOD CORPORATE GOVERNANCE - Gunawan Widjaja (JOURNAL OF LAW AND NATION, 2025)
This study discusses the organisational structure and management system of State-Owned Enterprises (SOEs) within the framework of implementing the principles of Good Corporate Governance (GCG). As state-owned business entities, SOEs play a strategic role in economic development and public services. However, the complexity of institutional relationships between the Minister as the representative of shareholders, the Board of Directors as operational managers, and the Board of Commissioners and Supervisory Board as internal controllers often causes problems in the implementation of effective and accountable governance. This study uses a literature review method by examining laws and regulations, academic literature, and institutional reports to analyse the roles and responsibilities of each SOE organ in realising good corporate governance. The results of the study show that the successful implementation of GCG in SOEs is highly dependent on the clarity of the division of functions and authorities, management integrity, and consistency in applying the principles of transparency, accountability, independence, responsibility, and fairness. Strong synergy between the Minister, the Board of Directors, the Board of Commissioners, and the Supervisory Board is necessary to create an efficient, professional management system that is oriented towards national sustainability.